The Effects of the Case-based Learning Method on Nursing Students’ Self-regulated Learning and Clinical Self-efficacy Perception: A Quasi-experimental Study. - Doğan, Nevin; Aksoy, Meyreme (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2026)
Background: Developing clinical self-efficacy (CSE) and self-regulated learning skills is essential for nursing students to navigate complex clinical environments and ensure safe patient care effectively. Aim: The purpose of this research was to explore how the case-based learning approach influences nursing students’ self-regulated learning abilities and their perceptions of CSE. Methods: This study employed a quasi-experimental design with a single-group pretest-posttest approach, conducted with 48 first-year nursing students from a public university in Türkiye. Over six weeks, participants engaged in weekly sessions based on the case-based learning model. Data were collected using three instruments: the Student Information Form, the Self-Regulated Learning Scale for Clinical Nursing Practice, and the Clinical Self-Efficacy Perception Scale. The collected data were analyzed using SPSS version 22.0, applying descriptive statistics, paired t-tests, and linear regression techniques. Results: Among the participants, 89.1% were female, with a mean age of 20.29±2.98 years. Following the intervention, no statistically significant difference was found in self-regulated learning scores (p>0.05); however, CSE perception scores showed a marked and statistically significant improvement (p<0.001). Regression analysis indicated that the predictive ability of self-regulated learning scores on CSE increased after the intervention, with explained variance rising from 11.2% at pretest to 16.3% at posttest. Conclusion: Case-based learning effectively enhances nursing students’ CSE, while the limited short-term gains in self-regulated learning highlight the need for sustained support. Developing both skills together is crucial for academic and professional success.